Correlation between iris color and glaucoma type - Kević, Angelina; Lisičić, Nikola; Božić, Marija (Medicinski podmladak, 2022)
Introduction: Glaucoma is a group of diseases, etiologically very different, which is characterized by typical damage to the optic nerve and visual field defects. The most common cause of this disease is higher intraocular pressure(IOP) than the vascular system of the optic nerve head can withstand.Aim: The aim of our study was to examine the correlation between iris color and glaucoma type through a cross-sectional study.           Material and methods: In 117 patients with glaucoma that were treated at the Clinic for Ophthalmology of the Clinical Center of Serbia, in the glaucoma clinic, relevant data was recorded, including iris color and the type of glaucoma that was diagnosed and under therapy. The correlation between iris color and sex of patients, age, type of glaucoma, values ​​of IOP of both eyes(IOP OD/OS) and central corneal thickness of both eyes(CCT OD/OS) was examined.Results: The population of our patients consisted of 38.5% men and 61.5% women. Primary open angle glaucoma(POAG) was present in 34.2% and primary angle closure glaucoma(PCAG) in 28.2% of patients. Blue iris was found in 16.2%, green in 6.8%, light brown in 29.9% and dark brown in 47% patients. The mean IOP is 17.6±6.5mmHg for the right and 16.9±6.1mmHg for the left eye, and for CCT 547.6±69.3μm for the right and 546.6±64.2μm for left eye. Statistically significant correlations were found between glaucoma type and sex(p = 0.001), glaucoma type and iris color(p = 0.031) and CCT and iris color(p = 0.027).Conclusion: A statistically significant correlation of iris color and glaucoma type was confirmed, indicating that people with darker irises develop glaucoma more often than people with lighter irises. We haven’t been able to determine the relationship between sex and IOP  with iris color. Our results show a higher incidence of glaucoma in females, as well as higher values ​​of CCT in people with darker irises.
Keywords: glaucoma, iris color, intraocular pressure, central corneal thickness